Resiliência e educação - Souza, Francisco das Chagas Silva; Almeida, Maria da Conceição Xavier de (Revista Educação em Questão, 2009)
CYRULNIK, Boris. Os patinhos feios. Tradução Monica Stahel. São Paulo: Martins Fontes, 2004. 215 p.